Gender Difference in Pain Management Among Adult Cancer Patients in Saudi Arabia: A Cross-Sectional Assessment - Alodhayani, Abdulaziz; Almutairi, Khalid M.; Vinluan, Jason M.; Alsadhan, Norah; Almigbal, Turky H.; Alonazi, Wadi B.; Batais, Mohammed Ali (Frontiers in Psychology, 2021)
Objective To compare gender differences in pain management among adult cancer patients in Saudi Arabia and to explore the predictors associated with attitudinal barriers of cancer patients to pain management. Methods A descriptive cross-sectional study was conducted among 325 cancer patients from tertiary hospitals in Saudi Arabia. Result Of the total participants, 67.4% were women (N = 219) and 32.6% were men (N = 106). The overall mean scores of the attitudinal barriers questionnaire were 49.51 ± 13.73 in men and 54.80 ± 22.53 in women. The analysis shows significant differences in scores in subscales of tolerance (men = 7.48 ± 2.37), (women = 8.41 ± 3.01) (p = 0.003) and fear of distraction in the course of treatment (men = 6.55 ± 1.34), and (women = 7.15 ± 2.63) (p = 0.008). Female patients reported a more moderate to severe level of pain than men (worst pain in last week of 7.07 ± 1.50, worst pain in last week of 5.84 ± 2.65, respectively). Splitting by gender, the significant predictor for physiology effect domains in male cancer patients includes age, marital status, employment status, monthly income, cancer type, and presence of comorbid disease (p < 0.050). Age was a significant predictor of the domains of fatalism, communication, and harmful effects (p < 0.050) among female cancer patients. Conclusion The present study revealed significant differences between men and women with attitudinal barriers to cancer pain management. Managing pain requires the involvement of all methods in a comprehensive manner, thus unalleviated pain influences the patient’s psychological or cognitive aspect.